PENDEDERAN NILA MERAH (Oreochromis niloticus) DENGAN SALINITAS BERBEDA - Verdian, Aldi Huda; Bokau , Rietje Juliana Marthina; Taufiq , Muhammad (Jurnal Perikanan Terapan, 2023)
Tilapia (Oreochromis niloticus) is one of the freshwater fishery commodities that is popular with the public and has high economic value, and has other advantages, namely that it is easy to cultivate and can adapt easily to various environmental conditions in fresh, brackish and marine waters. Tilapia is a euryhaline fish, where tilapia has good physiological adaptation to a wide range of salinity and has the ability to equalize salt levels in both sea and fresh water. Areas that have brackish saline waters are usually used as pond land with shrimp cultivation or milkfish cultivation as the main commodity. This research aims to determine the optimal salinity regarding the survival and growth of red tilapia in various salinities that are maintained for 30 days in order to increase the potential for greater production by utilizing less productive pond land to meet domestic and international market demand for tilapia. which is increasing. The use of rearing media with a salinity of 19 ppt produces a survival rate of 87.3 ± 0.98%, and produces an average final weight of 8.07 ± 0.02 grams with an average initial weight of 2.08 ± 0.02 grams. The final daily weight growth rate was 0.258 ± 0.0007 grams/day. The average final length is 11.67 ± 0.04 cm with an average initial length of 3,25 ± 0.21cm. Final daily length growth rate 0.351 ± 0 cm/day. SGR 4.14 ± 0.03%. And the lowest FCR with a salinity of 16 ppt was 1.23 ± 0.02. Based on experiments conducted, using a salinity of 19 ppt in the rearing media could increase the survival and growth rates of red tilapia.